2022
DOI: 10.3389/fmed.2022.940159
|View full text |Cite
|
Sign up to set email alerts
|

Serial platelet level index improves prediction of pulmonary hemorrhage in patients with Stenotrophomonas maltophilia respiratory infections and thrombocytopenia

Abstract: Patients with thrombocytopenia (platelet count <150 × 103/μL) often develop pulmonary hemorrhage (PH) after Stenotrophomonas maltophilia (SM) respiratory infection, resulting in a high respiratory failure rate and increased mortality. Developing an efficient method for early prediction of PH in these patients may improve survival. This study aimed to evaluate risk factors in PH and to develop an index measuring serial platelet deficit to predict PH in patients with SM respiratory infection. Data of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…et al showed that patients with Stenotrophomonas maltophilia respiratory infections often experience thrombocytopenia, which is an independent risk factor for pulmonary hemorrhage and mortality. The author suggested that this group of patients may benefit from a prophylactic platelet transfusion on a regular basis to keep their platelet counts above a certain threshold over unstable periods and may be a potential strategy to serve as a preventative measure against pulmonary hemorrhage [43]. Overall, the current investigation verified that hemorrhagic pneumonia risk factors included thrombocytopenia.…”
Section: Thrombocytopenia Is a Risk Factor For Hemorrhagic Pneumonia ...supporting
confidence: 52%
“…et al showed that patients with Stenotrophomonas maltophilia respiratory infections often experience thrombocytopenia, which is an independent risk factor for pulmonary hemorrhage and mortality. The author suggested that this group of patients may benefit from a prophylactic platelet transfusion on a regular basis to keep their platelet counts above a certain threshold over unstable periods and may be a potential strategy to serve as a preventative measure against pulmonary hemorrhage [43]. Overall, the current investigation verified that hemorrhagic pneumonia risk factors included thrombocytopenia.…”
Section: Thrombocytopenia Is a Risk Factor For Hemorrhagic Pneumonia ...supporting
confidence: 52%